PipC affects the virulence of Salmonella enterica serovar Enteritidis and its deletion strain provides effective immune protection in mice - Zhang, Lu; Chen, Yubin; Yan, Zhigang; Li, Yuntai; Yang, Xiaowen; Chen, Li; Zhang, Yanying; Chen, Yingyu; Li, Yonghui; Shi, Qiumei; Wu, Tonglei (Frontiers in Microbiology, 2025)
BackgroundSalmonellosis caused by Salmonella sp. is a foodborne zoonotic disease that poses a significant threat to public health security. Vaccination is a safe and effective strategy for preventing and controlling Salmonella infections. PipC is a chaperone protein associated with Salmonella invasion proteins which is crucial for bacteria to invade host cells.MethodsIn this study, a ΔpipC mutant strain was generated. Subsequently, we examined the environmental stress tolerance of the mutant strain through in vitro simulation experiments. Moreover, its virulence by employing cell and mouse infection models was investigated. Furthermore, we utilized a mouse model to further explore its potential as an attenuated live vaccine against Salmonella enterica serovar Enteritidis infection.ResultsThe Salmonella strain C50336 with a deletion of the pipC gene exhibits a significant reduction in its ability to resist environmental stress and virulence. Meanwhile, the expression levels of SPI-1-related genes (invH, sipA, sipB, sipC, sopB, and sopE2) and SPI-2-related genes (spvB, ssrA, orf245, ssaS, ssaT, ssaU, sseB, and sseD) encoding the Salmonella type III secretion system (T3SS) were found to be decreased, leading to a significant reduction in the bacteria’s invasion and intracellular survival abilities. The results of the mouse intraperitoneal challenge experiment showed that compared with the wild-type strain, the 50% lethal dose (LD50) of the ΔpipC strain increased by 47 times, and the bacterial loads in the liver, spleen, and cecum were significantly reduced. When mice were immunized with the ΔpipC mutant strain, the immunized mice showed a robust immune response, with significantly increased cytokine and antibody levels in their bodies. Mice vaccinated with the ΔpipC mutant strain had 100% immune protection against wild-type Salmonella infection.ConclusionThis study demonstrates that lack of pipC affects SE pathogenicity by decreasing its virulence both in vitro and in vivo. Vaccination of mice with ΔpipC conferred development of an acquired immunity and efficacious protection against experimental systemic infection. These results indicated that the ΔpipC mutant strain can be used in the development of attenuated live vaccines.